2018
DOI: 10.1021/acs.jpcb.8b01287
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Aztreonam Hydrolysis Catalyzed by Class-C β-Lactamase: A Temperature-Accelerated Sliced Sampling Study

Abstract: Enhanced sampling of large number of collective variables (CVs) is inevitable in molecular dynamics (MD) simulations of complex chemical processes such as enzymatic reactions. Because of the computational overhead of hybrid quantum mechanical/molecular mechanical (QM/MM)-based MD simulations, especially together with density functional theory, predictions of reaction mechanism, and estimation of free-energy barriers have to be carried out within few tens of picoseconds. We show here that the recently developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…Temperature of the auxiliary variables was set to 1,000 K, while the system temperature was kept at 300 K. In total, 16 umbrella windows were placed at equal distance from 1.3 to 2.9 Å along CV1. It was observed that the free energy barrier converges within 9 ps (per umbrella window) . The converged free energy surface was computed using the reweighting procedure explained in Reference 146 and then projected to CV1 and CV2 as shown in Figure .…”
Section: Temperature‐accelerated Sliced Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature of the auxiliary variables was set to 1,000 K, while the system temperature was kept at 300 K. In total, 16 umbrella windows were placed at equal distance from 1.3 to 2.9 Å along CV1. It was observed that the free energy barrier converges within 9 ps (per umbrella window) . The converged free energy surface was computed using the reweighting procedure explained in Reference 146 and then projected to CV1 and CV2 as shown in Figure .…”
Section: Temperature‐accelerated Sliced Samplingmentioning
confidence: 99%
“…Protein backbone is shown as transparent ribbons. (Reprinted with permission from Reference . Copyright 2018 American Chemical Society)…”
Section: Temperature‐accelerated Sliced Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In fact, this is also seen in the computational study on aztreonam (which is a β-lactam inhibitor) with class C β-lactamase. 17 Many other works further proposed mechanistic details of reverse acylation, considering it to be kinetically preferable over hydrolysis. [18][19][20][21] Based on point mutational studies 18,19 and high-resolution crystal structure captured by Lahiri et al, 20 a general base catalyzed mechanism is suggested for the recyclization of avibactam.…”
mentioning
confidence: 99%
“…See, for example, Refs. (Das and Paul, 2017;Chand et al, 2018;Dasari and Mallik, 2018;Kaur and Kashyap, 2018;Awasthi et al, 2016;Awasthi and Nair, 2017;Awasthi et al, 2018;Chugh and Ranganathan, 2016;Ghosh and Ranganathan, 2017;Chugh and Ranganathan, 2017;Sarkar et al, 2019;Maity and Reddy, 2018;Nandi et al, 2017;Hridya and Mukherjee, 2018;Sharma and Ghorai, 2018;Ahalawat and Murarka, 2017;Rout and Srinivasan, 2018;Shekar and Swathi, 2018;Kumawat and Chakrabarty, 2017;Palchowdhury and Bhargava, 2018;Mandal et al, 2018;Ahalawat and Mondal, 2018;Hasnain and Bandyopadhyay, 2015;Dutta and Nandi, 2015) for representative work from these groups in recent years. Also, many institutes now have multiple research groups working in statistical mechanics and computer simulations.…”
mentioning
confidence: 99%